Photocatalytic Degradation of Reactive Yellow in Batch and Continuous Photoreactor Using Titanium Dioxide (Journal of Scientific Research, 2012)
Titanium dioxide (TiO2) has been used as photo-catalyst for the degradation of reactive yellow (RY) in batch and continuous mode under UV irradiation. Titanium dioxide (TiO2) was immobilized onto the ceramic plate using cement as binder. The effects of various parameters such as initial dye concentration, solution layer thickness, presence of catalyst, residence time, and catalyst loading on degradation have been investigated. The results showed that without catalyst no degradation was achieved. The maximum sorption capacity of TiO2 was found to be 0.01447 kg/kg. The degradation of RY followed pseudo-first order kinetics with rate constant k = 0.001 min-1. A decrease in degradation of RY was observed with an increase in initial concentration and solution layer thickness. A comparison of photocatalytic performance between batch and continuous mode was performed and the batch mode provided better degradation performance. About 60% degradation of dye was achieved at 360 min for 200 ppm RY solution in batch mode.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i3.8654 J. Sci. Res. 4 (3), 665-674 (2012)